A framework for exhaustively mapping functional missense variants. Issue 12 (21st December 2017) - Weile, Jochen; Sun, Song; Cote, Atina G; Knapp, Jennifer; Verby, Marta; Mellor, Joseph C; Wu, Yingzhou; Pons, Carles; Wong, Cassandra; van Lieshout, Natascha; Yang, Fan; Tasan, Murat; et al.
Abstract: Although we now routinely sequence human genomes, we can confidently identify only a fraction of the sequence variants that have a functional impact. Here, we developed a deep mutational scanning framework that produces exhaustive maps for human missense variants by combining random codon mutagenesis and multiplexed functional variation assays with computational imputation and refinement. We applied this framework to four proteins corresponding to six human genes: UBE2I (encoding SUMO E2 conjugase), SUMO1 (small ubiquitin‐like modifier), TPK1 (thiamin pyrophosphokinase), and CALM1/2/3 (three genes encoding the protein calmodulin). The resulting maps recapitulate known protein features and confidently identify pathogenic variation. Assays potentially amenable to deep mutational scanning are already available for 57% of human disease genes, suggesting that DMS could ultimately map functional variation for all human disease genes. Synopsis: A new framework combining random codon‐mutagenesis and multiplexed functional variation assays with computational imputation, allows the comprehensive identification of functional missense variation. The approach is applied to identify pathogenic variation in six human genes. A modular deep mutational scanning (DMS) framework combines random codon‐mutagenesis and multiplexed functional variation assays with computational imputation and refinement. The framework is applied to four human proteins corresponding to six human genes and generates comprehensive functional variation maps covering > 13, 000 missense variants. These maps confidently identify pathogenic variation. DMS is a promising approach for generating exhaustive maps of functional variation covering all human genes. Abstract : A new framework combining random codon‐mutagenesis and multiplexed functional variation assays with computational imputation, allows the comprehensive identification of functional missense variation. The approach is applied to identify pathogenic variation in six human genes.